Client-Server Approach for Managing Visual Attention, Integrated in a Cognitive Architecture for a Social Robot - Martín, Francisco; Ginés, Jonatan; Rodríguez-Lera, Francisco J.; Guerrero-Higueras, Angel M.; Matellán Olivera, Vicente (Frontiers in Neurorobotics, 2021)
This paper proposes a novel system for managing visual attention in social robots. This system is based on a client/server approach that allows integration with a cognitive architecture controlling the robot. The core of this architecture is a distributed knowledge graph, in which the perceptual needs are expressed by the presence of arcs to stimuli that need to be perceived. The attention server sends motion commands to the actuators of the robot, while the attention clients send requests through the common knowledge representation. The common knowledge graph is shared by all levels of the architecture. This system has been implemented on ROS and tested on a social robot to verify the validity of the approach and was used to solve the tests proposed in RoboCup @ Home and SciROc robotic competitions. The tests have been used to quantitatively compare the proposal to traditional visual attention mechanisms.